[Crowd listening to MLK event speakers?] (1984)
The crowd is sitting on the concrete stairs in the University Union plaza. Some students are in the back and sitting at tables or under trees. In the back hanging from the Union's second story railing, there are signs that read '- Payback. This week only!' and 'SCE Meeting WED 7:30PM'.